Manufacturing method for RTB sintered magnets
By using wetted nitrogen during the grinding process of R-T-B ingot magnets, controlling the oxygen content and modifying the powder surface, the problem of difficult to take into account both grinding efficiency and magnetic properties in the prior art is solved, and a combination of efficient grinding and high magnetic properties is achieved.
Patent Information
- Application Number
- JP2021137689
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-24
- Filing Date
- 2021-08-26
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-12-24
AI Technical Summary
In the prior art, when manufacturing R-T-B ingot magnets, it is difficult to maintain grinding efficiency while improving magnetic properties, and grinding technology with high oxygen content cannot be applied to high-performance magnets.
Wet nitrogen is used as the grinding gas, and the oxygen content is controlled between 1000 ppm and 3500 ppm during the grinding process. The powder surface is modified by wet nitrogen to prevent the powder from oxidizing or nitriding due to nitrogen grinding, thereby maintaining the grinding efficiency and improving magnetic properties.
While maintaining the grinding efficiency, the magnetic properties of the R-T-B ingot magnet are improved, and the oxidation or nitriding problems caused by the grinding of the powder are avoided, and the overall performance of the magnet is improved.
Smart Images

Figure 0007661831000014 
Figure 0007661831000001 
Figure 0007661831000002
Abstract
Description
[Technical field]
[0001] The present application relates to a method for producing an RTB based sintered magnet, and to an RTB based sintered magnet. [Background technology]
[0002] RTB sintered magnets (R is a rare earth element and must contain at least one selected from the group consisting of Nd, Pr and Ce, T is at least one transition metal and must contain Fe, and B is boron) are represented by the formula RFe 14 It is composed of a main phase of a compound having a B-type crystal structure, a grain boundary phase located at the grain boundaries of this main phase, and a compound phase formed by the influence of trace additive elements and impurities, and has a high residual magnetic flux density B r (Hereinafter, simply "B r ") and high coercivity H cJ (Hereafter, simply "H cJ "), and has excellent magnetic properties, making it known as the highest performance magnet among permanent magnets. For this reason, it is used in a wide variety of applications, including voice coil motors (VCM) for hard disk drives, motors for electric vehicles (EV, HV, PHV), motors for industrial equipment, and various other motors and home appliances.
[0003] Such an RTB based sintered magnet is manufactured, for example, through the steps of preparing an alloy powder, press-molding the alloy powder to produce a powder compact, and sintering the powder compact. The alloy powder is manufactured, for example, by the following method.
[0004] First, an alloy is produced from molten metals of various raw materials by an ingot method, strip casting method, or the like. The obtained alloy is subjected to a pulverization process to obtain an alloy powder having a predetermined particle size distribution. This pulverization process usually includes a coarse pulverization process and a fine pulverization process, the former of which is carried out by utilizing, for example, the hydrogen embrittlement phenomenon, and the latter of which is carried out by using, for example, an airflow pulverizer (jet mill).
[0005] The alloy powder obtained by such a pulverization step is subjected to solid-gas separation, for example, by a cyclone-type collector, and the alloy powder for RTB sintered magnets is recovered (collected).
[0006] There is a demand for RTB sintered magnets with even higher performance and lower costs. Methods for improving performance include, for example, making the structure finer and reducing the amount of oxygen contained, while methods for reducing costs include, for example, improving the efficiency of pulverization. Patent Document 1 discloses a method for improving pulverization efficiency in which jet mill pulverization is performed using a humidified inert gas stream with a dew point of -20°C to 0°C. A similar method is also described in Patent Document 2. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 8-148317 [Patent Document 2] Japanese Patent Application Publication No. 6-140220 Summary of the Invention [Problem to be solved by the invention]
[0008] The oxygen content has been reduced, for example, the oxygen content is 3500 ppm or less by mass. 14 When producing an RTB sintered magnet in which the B phase is the main phase, for example, high purity nitrogen gas is used as the inert gas to prevent oxidation of the powder particles during the pulverization process.
[0009] According to the study by the present inventors, it was found that when jet mill grinding is performed using an inert gas such as high-purity nitrogen gas, the expected high performance cannot be achieved by reducing the oxygen content. In addition, when trying to improve performance by finely grinding the powder, the grinding efficiency is sacrificed. Regarding the grinding efficiency, there are methods disclosed in Patent Documents 1 and 2, but the configurations disclosed in Patent Documents 1 and 2 are technologies for increasing the oxygen content to more than 4500 ppm in order to suppress reactivity, and cannot be applied to improving performance by reducing oxygen content. The embodiments of the present disclosure provide a manufacturing method for an RTB-based sintered magnet and an RTB-based sintered magnet that can solve such problems. [Means for solving the problem]
[0010] In a non-limiting exemplary embodiment, a method for producing an RTB based sintered magnet according to the present disclosure is a method for producing an RTB based sintered magnet (wherein R is a rare earth element and necessarily includes at least one selected from the group consisting of Nd, Pr, and Ce, and T is at least one transition metal and necessarily includes Fe), comprising the steps of: preparing a coarsely pulverized powder of an alloy for the RTB based sintered magnet, the coarsely pulverized powder having an average particle size of 10 μm or more and 500 μm or less; supplying the coarsely pulverized powder to a jet mill device having a grinding chamber filled with an inert gas to grind the coarsely pulverized powder to obtain a fine powder having an average particle size of 2.0 μm or more and 4.5 μm or less; and producing a sintered body of the fine powder, wherein the inert gas is humidified, and the RTB based sintered magnet has an oxygen content of 1000 ppm or more and 3500 ppm or less by mass.
[0011] In one embodiment, the RTB based sintered magnet has an R content of 31 mass % or less.
[0012] In one embodiment, the inert gas is nitrogen gas.
[0013] In one embodiment, the method further includes a diffusion step of diffusing a heavy rare earth element RH (RH is at least one of Tb, Dy, and Ho) from the surface of the sintered body to the inside.
[0014] In one embodiment, the step of producing a sintered body of the fine powder includes a step of producing a powder compact from the fine powder by wet pressing in a magnetic field or pressing in a magnetic field in an inert gas atmosphere, and a step of sintering the powder compact.
[0015] In one embodiment, the average particle size of the fine powder in the step of obtaining the fine powder is 2.0 μm or more and 3.5 μm or less.
[0016] In a non-limiting exemplary embodiment, the RTB based sintered magnet of the present disclosure is an RTB based sintered magnet (R is a rare earth element and necessarily includes at least one selected from the group consisting of Nd, Pr, and Ce, and T is at least one transition metal and necessarily includes Fe), and the main phase of the RTB based sintered magnet is R2T 14 The average crystal grain size of phase B is 3 μm or more and 7 μm or less, and contains oxygen, carbon, and nitrogen. The oxygen content is 1000 ppm or more and 3500 ppm or less in mass ratio, the carbon content is 80 ppm or more and 1500 ppm or less in mass ratio, and the nitrogen content is 50 ppm or more and 600 ppm or less in mass ratio. When the oxygen content is [O], the carbon content is [C], and the nitrogen content is [N] in mass ratio, the following formulas 1 to 3 are satisfied. Equation 1: [O]>[C]>[N] Equation 2: [O]≧1.5×[N] Equation 3: [C]≧1.5×[N]
[0017] In a non-limiting exemplary embodiment, the RTB based sintered magnet of the present disclosure is 14 An RTB sintered magnet comprising a main phase made of a B compound and a grain boundary phase located at the grain boundaries of the main phase (R is a rare earth element and necessarily includes at least one selected from the group consisting of Nd, Pr and Ce, and T is at least one transition metal and necessarily includes Fe), wherein the main phase of the RTB sintered magnet is R2T 14The average crystal grain size of phase B is 3 μm or more and 7 μm or less, the RTB based sintered magnet contains oxygen, carbon, and nitrogen, the oxygen content is 1000 ppm or more and 3500 ppm or less by mass, and the nitrogen content is 50 ppm or more and 600 pm or less by mass, the grain boundary phase has a rare earth oxide phase which includes a rare earth oxynitride phase having a NaCl-type crystal structure, and where the O content (atomic %) in the rare earth oxynitride phase is {O} and the N content (atomic %) in the rare earth oxynitride phase is {N}, the relationship {O}>1.8×{N} is satisfied.
[0018] In one embodiment, the RTB based sintered magnet satisfies the relationship {C}>{N}×0.5, where {C} is the C content (atomic %) in the rare earth oxynitride phase.
[0019] In one embodiment, in any cross section of the RTB based sintered magnet, the ratio of the area of the rare earth oxynitride phase to the area of the rare earth oxide phase is 50% or more.
[0020] In one embodiment, the RTB based sintered magnet includes a portion in which at least one of the Tb concentration and the Dy concentration gradually decreases from the magnet surface toward the magnet interior. Effect of the Invention
[0021] According to the embodiment of the present disclosure, the particle surfaces of the fine powder obtained by jet mill pulverization can be appropriately modified by a humidified inert gas, which makes it possible to suppress deterioration of the pulverization efficiency during jet mill pulverization even if the pulverized particle size of the fine powder is reduced, and ultimately realize an RTB-based sintered magnet with excellent magnetic properties. [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 is a diagram showing a schematic configuration example of an RTB sintered magnet alloy crushing system 1000 according to this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] As a result of the study, the inventors of the present invention found that, in the case of producing an RTB-based sintered magnet with a reduced oxygen content, in addition to the deterioration of the grinding efficiency, when the powder particles are reduced in size in the grinding process, the powder particles are deteriorated (nitrided) by an inert gas (particularly when dry nitrogen gas is used as the inert gas) in the grinding process, and the desired improvement in magnetic properties due to the reduction in the size of the ground particles cannot be obtained. As a result of further study, the inventors of the present invention found that the deterioration of powder particles due to the inert gas can be reduced by using a humidified inert gas. This is believed to be because the formation of an oxide film on the surface of the powder particles makes it possible to prevent the introduction of an inert gas (particularly nitrogen gas) into the powder particles, thereby suppressing the deterioration (nitridation) of the powder particles due to the inert gas. It has been known in the past that the grinding efficiency is deteriorated when the powder particles are reduced in size in the grinding process, and that this deterioration can be improved by using a humidified inert gas flow (for example, Patent Document 1 and Patent Document 2). However, it is natural that the powder particles are oxidized and the magnetic properties are deteriorated when the powder particles are ground using a humidified inert gas flow. Therefore, when manufacturing an RTB-based sintered magnet with a reduced oxygen content to improve magnetic properties, pulverization using a humidified inert gas stream has not been actively carried out in an attempt to make the pulverized particles smaller (for example, the oxygen content of the fine powder in Patent Document 1 is relatively high at 4500 ppm and 4900 ppm by mass, while Patent Document 2 does not disclose the oxygen content). However, the present inventors conducted extensive research based on the above-mentioned knowledge that the deterioration of powder particles due to inert gas can be reduced by using a humidified inert gas, and as a result, they unexpectedly found that, in the final RTB-based sintered magnet, when the powder particles are humidified and pulverized so that the oxygen content is within a specific range that reduces the oxygen content, it is possible to suppress both the deterioration (nitridation) of the powder particles and the decrease in magnetic properties due to oxidation caused by humidification. Note that, in the process after pulverization, the oxygen content of the RTB-based sintered magnet is usually increased mainly in the process of forming and sintering the fine powder to produce a sintered body, but the increase in the oxygen content of the RTB-based sintered magnet is small (for example, 50 ppm to 300 ppm by mass). Therefore, the oxygen content of the RTB sintered magnet can be adjusted by the crushing process.That is, in the present disclosure, in the pulverization process, humid pulverization is performed so that the oxygen content of the obtained R-T-B sintered magnet is within a specific range (1000 ppm or more and 3500 ppm or less, preferably 1000 ppm or more and 3200 ppm or less) to reduce the size of powder particles (the average particle size is 2.0 μm or more and 4.5 μm or less, preferably the average particle size is 2.0 μm or more and 3.5 μm or less). As a result, the pulverizability can be improved, and by reducing the deterioration of magnetic properties due to oxidation or nitridation in the pulverization process, it has been found that an R-T-B sintered magnet having high magnetic properties can be obtained. Also, in this way, R2T which is the main phase of the R-T-B sintered magnet. 14 The average crystal grain size of the B phase is 3 μm or more and 7 μm or less, it contains oxygen, carbon, and nitrogen, the oxygen content is 1000 ppm or more and 3500 ppm or less by mass ratio, the carbon content is 80 ppm or more and 1500 ppm or less by mass ratio, and the nitrogen content is 50 ppm or more and 600 ppm or less by mass ratio. When the oxygen content by mass ratio is [O], the carbon content is [C], and the nitrogen content is [N], an R-T-B sintered magnet that satisfies the following formulas 1 to 3 can be preferably obtained. Formula 1: [O] > [C] > [N] Formula 2: [O] ≥ 1.5 × [N] Formula 3: [C] ≥ 1.5 × [N]
[0024] <Method for manufacturing an R-T-B sintered magnet> Hereinafter, embodiments of the method for manufacturing an R-T-B sintered magnet according to the present disclosure will be described.
[0025] The present disclosure is a method for manufacturing an R-T-B sintered magnet. Here, R is a rare earth element and necessarily contains at least one selected from the group consisting of Nd, Pr, and Ce, and T is at least one transition metal and necessarily contains Fe.
[0026] This method for manufacturing an R-T-B sintered magnet is (1) A step of preparing a coarse pulverized powder of an alloy for an R-T-B sintered magnet having an average particle size of 10 μm or more and 500 μm or less, (2) Supply the coarsely pulverized powder to a jet mill device filled with an inert gas to pulverize the coarsely pulverized powder, and obtain a fine powder having an average particle size of 2.0 μm or more and 4.5 μm or less; (3) A step of producing a sintered body of the fine powder; including, the inert gas is humidified. The average particle size (d50) can be measured by the air flow dispersion type laser diffraction method.
[0027] <R-T-B sintered magnet> The R-T-B sintered magnet of the present disclosure has an oxygen content of 1000 ppm or more and 3500 ppm or less by mass ratio. By setting the oxygen content to 1000 ppm or more and 3500 ppm or less, in the step of obtaining the fine powder in (2) above, deterioration (nitridation) of powder particles due to the inert gas progresses due to the humidity of the inert gas being too weak. It is possible to suppress a decrease in magnetic properties due to oxidation of powder particles due to humidity. In order to obtain higher magnetic properties, the oxygen content of the R-T-B sintered magnet is preferably 1000 ppm or more and 3200 ppm or less, more preferably 1000 ppm or more and 2400 ppm or less, and even more preferably 1300 ppm or more and 2400 ppm or less. Further, through pulverization by humidification, by setting the oxygen content (1000 ppm or more and 3500 ppm or more) of the R-T-B sintered magnet as in the present disclosure, as shown in the examples described later, the compressibility in molding can be improved. By improving the compressibility, molding can be performed at a lower molding pressure. As a result, it is possible to suppress the generation of cracks in the molded body. Furthermore, since it is possible to improve the continuous moldability by reducing the load on the mold and reduce the frequency of mold repair, the production efficiency can be improved. Preferably, the oxygen content of the R-T-B sintered magnet is 2000 ppm or more. The moldability can be further improved. Therefore, considering the moldability and magnetic properties (B r and H cJ ), the oxygen content of the R-T-B sintered magnet is preferably 2000 ppm or more and 2400 ppm or less.
[0028] The following shows the composition of a preferable R-T-B sintered magnet.
[0029] R is a rare earth element and must include at least one selected from the group consisting of Nd, Pr and Ce. Preferably, a combination of rare earth elements represented by Nd-Dy, Nd-Tb, Nd-Dy-Tb, Nd-Pr-Dy, Nd-Pr-Tb and Nd-Pr-Dy-Tb is used.
[0030] Among R, Dy and Tb are particularly cJ It is effective in improving the above-mentioned elements. In addition to the above elements, other rare earth elements such as La may be contained, and misch metal or didymium may also be used. Furthermore, R does not have to be a pure element, and may contain impurities that are unavoidable in the manufacturing process within the range of industrial availability. The content is, for example, 27% by mass or more and 35% by mass or less. The R content of the RTB sintered magnet is preferably 31% by mass or less (27% by mass or more and 31% by mass or less, preferably 29% by mass or more and 31% by mass or less). By making the R content of the RTB sintered magnet 31% by mass or less and the oxygen content 1000 ppm by mass or more and 3500 ppm by mass or less, the generation of R oxidized by humidification during humidified grinding is reduced. Therefore, higher magnetic properties can be obtained.
[0031] T contains iron (including the case where T is substantially composed of iron), and up to 50% by mass of iron may be replaced with cobalt (Co) (including the case where T is substantially composed of iron and cobalt). Co is effective for improving temperature characteristics and corrosion resistance, and the alloy powder may contain up to 10% by mass of Co. The content of T may be the remainder of R and B, or R, B, and M described below.
[0032] The content of B may be a known content, and for example, a preferred range is 0.9% by mass to 1.2% by mass. If it is less than 0.9% by mass, high H cJ If it exceeds 1.2 mass%, B may not be obtained. r In addition, a part of B can be substituted with C (carbon). The content is more preferably 1.0 mass % or less, and further preferably 0.96 mass % or less.
[0033] In addition to the above elements, H cJ In order to improve the properties, an M element can be added. The M element is one or more selected from the group consisting of Al, Si, Ti, V, Cr, Mn, Ni, Cu, Zn, Ga, Zr, Nb, Mo, In, Sn, Hf, Ta and W. The amount of M element added is preferably 5.0 mass% or less. If it exceeds 5.0 mass%, Br may decrease. Inevitable impurities are also acceptable.
[0034] The N (nitrogen) content in the RTB sintered magnet is preferably 50 ppm or more and 600 ppm or less by mass. By performing humidified grinding so that the N (nitrogen) content is 50 ppm or more and 600 ppm or less by mass, it is possible to improve the grindability while suppressing the deterioration of the magnetic properties due to nitriding. The nitrogen content is more preferably 50 ppm or more and 400 ppm or less, and most preferably 100 ppm or more and 300 ppm or less. This is because it is possible to further improve the grindability while suppressing the deterioration of the magnetic properties due to nitriding. Furthermore, the C (carbon) content in the RTB sintered magnet is preferably 80 ppm or more and 1500 ppm or less by mass, and more preferably 80 ppm or more and 1000 ppm or less. Furthermore, the lower limit of the C content can be set to 500 ppm, and can also be set to 800 ppm or more. Furthermore, the RTB sintered magnet of the present disclosure preferably satisfies the following formulas 1 to 3, where the oxygen content is [O], the carbon content is [C], and the nitrogen content is [N], in mass ratio. Equation 1: [O]>[C]>[N], Equation 2: [O]≧1.5×[N], Equation 3: [C]≧1.5×[N]
[0035] By satisfying the above formulas 1 to 3, an RTB sintered magnet can be obtained that can more reliably improve pulverizability and simultaneously suppress the deterioration of powder particles and the deterioration of magnetic properties due to oxidation caused by humidification. As described above, the RTB sintered magnet of the present disclosure has an increased oxygen content by humidification pulverization, but nitridation caused by pulverization is particularly suppressed. As a result, the oxygen, carbon, and nitrogen contents in the obtained RTB sintered magnet can be made to satisfy formula 1 ([O]>[C]>[N]). Furthermore, by sufficiently suppressing nitridation, the nitrogen content becomes smaller than the oxygen and carbon contents, and formula 2 ([O]≧1.5×[N]) and formula 3 ([C]≧1.5×[N]) can be made to satisfy formula 2 ([O]≧3×[N], [O]≧5×[N] is even more preferable, and [O]≧10×[N] is most preferable. Furthermore, formula 3 is more preferably [C]≧2×[N] and most preferably [C]≧5×[N].
[0036] In addition, the R2T, which is the main phase of the RTB based sintered magnet of the present disclosure, 14 The average crystal grain size of the B phase is 3.5 μm or more and 7.0 μm or less. The average crystal grain size can be determined by the number average of the equivalent circle diameters of crystal grains (5000 or more) evaluated by EBSD (Electron Backscatter Diffraction).
[0037] <(1) Example of a process for preparing coarsely pulverized powder of alloy for RTB sintered magnets with an average particle size of 10 μm to 500 μm> The process of preparing a coarsely pulverized powder of an alloy for an RTB based sintered magnet having an average particle size of 10 μm or more and 500 μm or less includes a process of preparing an alloy for an RTB based sintered magnet and a process of coarsely pulverizing this alloy by, for example, a hydrogen pulverization method.
[0038] Here is an example of a method for producing an alloy for an RTB sintered magnet. An alloy ingot can be obtained by ingot casting, in which a metal or alloy previously adjusted to have the above-mentioned composition is melted and poured into a mold. In addition, alloy flakes can be produced by a quenching method, typically a strip casting method or a centrifugal casting method, in which the molten metal is brought into contact with a single roll, a twin roll, a rotating disk, or a rotating cylindrical mold, and quenched to produce a solidified alloy that is thinner than the alloy produced by the ingot method.
[0039] In the embodiment of the present disclosure, materials produced by either the ingot method or the quenching method can be used, but it is preferable to produce the alloy by a quenching method such as a strip casting method. The thickness of the quenched alloy produced by the quenching method is usually in the range of 0.03 mm to 1 mm, and it is in a flake shape. The molten alloy starts to solidify from the surface (roll contact surface) that contacts the cooling roll, and crystals grow columnarly from the roll contact surface in the thickness direction. The quenched alloy is cooled in a short time compared to the alloy (ingot alloy) produced by the conventional ingot casting method (mold casting method), so the structure is finer and the crystal grain size is smaller. In addition, the area of the grain boundary is large. Since the R-rich phase spreads widely within the grain boundary, the quenching method has excellent dispersibility of the R-rich phase. Therefore, it is easy to break at the grain boundary by the hydrogen pulverization method. By hydrogen pulverizing the quenched alloy, the size of the hydrogen pulverized powder (coarse pulverized powder) can be reduced to, for example, 1.0 mm or less. The coarse pulverized powder obtained in this manner is pulverized by a jet mill in a humidified atmosphere (step (2)).
[0040] <(2) An example of a process in which coarsely pulverized powder is supplied to a jet mill device whose pulverizing chamber is filled with an inert gas, and the coarsely pulverized powder is pulverized to obtain a fine powder having an average particle size of 2.0 μm to 4.5 μm.> <Crushing system> First, a pulverization system that can be used in the manufacturing method of the RTB sintered magnet according to the present disclosure will be described with reference to Fig. 1. Fig. 1 is a diagram showing a schematic configuration example of a pulverization system 1000 in this embodiment. In this example, the RTB sintered magnet alloy pulverization system 1000 includes a jet mill device 100, a cyclone collection device 200, and a bag filter device 300.
[0041] The jet mill device 100 receives the material to be pulverized from a raw material tank (not shown) via a raw material input pipe 34. The material to be pulverized is a coarsely pulverized powder of an alloy for an RTB sintered magnet, the average particle size of which is 10 μm or more and 500 μm or less. The average particle size (d50) in this disclosure can be measured by an airflow dispersion type laser diffraction method (compliant with JIS Z 8825: 2013 revised edition). That is, in this specification, the average particle size means the particle size (median diameter) at which the cumulative particle size distribution (volume basis) from the small particle size side is 50%.
[0042] In the embodiments of the present disclosure, the average particle size (d50) refers to the d50 measured using a particle size distribution measuring device "HELOS&RODOS" manufactured by Sympatec under the following conditions: dispersion pressure: 4 bar, measurement range: R2, calculation mode: HRLD.
[0043] The raw material input pipe 34 is provided with multiple valves, and the internal pressure of the jet mill device 100 is appropriately maintained by opening and closing the valves. The material to be pulverized introduced into the jet mill device 100 is finely pulverized by collisions between the materials to be pulverized due to high-speed jets of inert gas from the nozzle pipe 36 and collisions with a collision plate installed to efficiently advance the pulverization. A humidification pipe is connected to the nozzle pipe 36 to add moisture to the inert gas.
[0044] Powder of alloys for RTB sintered magnets is active and easily oxidized. For this reason, as the gas used in the jet mill device 100, in order to avoid the risk of heat generation and fire and to reduce the oxygen content as an impurity to improve the performance of the magnet, dry (high purity) inert gases such as nitrogen, argon, and helium with a dew point of -60°C or less are generally used. However, in the embodiment of the present disclosure, the grinding is performed in a humidified state in which moisture is intentionally introduced into such inert gas. Details of this point will be described later.
[0045] The powder particles (fine powder) finely pulverized inside the jet mill device 100 are carried by the ascending air current and guided from the upper outlet 40 to the inlet pipe 20 of the cyclone collector 200. Coarse particles that are not sufficiently pulverized are separated by a classifying rotor installed to classify coarse particles with a median diameter (d50) or more, remain inside the jet mill device 100, and are subjected to a further crushing process by collision. The classification of these coarse particles may be performed using a classifying rotor or centrifugal separation using a swirling flow. In this way, the material to be pulverized (coarsely pulverized powder) fed into the jet mill device 100 is pulverized into fine powder with a particle size distribution of 2.0 μm to 4.5 μm in average particle size (median diameter: d50) before being transferred to the cyclone collector 200.
[0046] The cyclone collector 200 is used to separate the powder from the airflow carrying the powder. Specifically, coarsely pulverized powder of an alloy for RTB-based sintered magnets is pulverized in a jet mill at a front stage, and the fine powder generated by the pulverization is supplied to the cyclone collector 200 through an inlet pipe 20 together with the gas used for the pulverization. A mixture of an inert gas (pulverization gas) and the pulverized fine powder forms a high-speed airflow and is sent to the cyclone collector 200. The cyclone collector 200 is used to separate the pulverization gas from the fine powder. The fine powder separated from the pulverization residue is collected by a powder collector 50 through an outlet 40. The pulverization gas is supplied to a bag filter device 300 through an outlet pipe 30. The bag filter device 300 collects very small particles, and clean gas is discharged to the outside through an exhaust port 32. For such solid-gas separation, it is possible to use a bag filter instead of the cyclone collector 200, but this would have a large impact on the environment and safety, such as the dispersion of fine powder into the air due to damage to the filter. A bag filter may also be used to separate fine particles from the gas separated by the cyclone collector 200.
[0047] A characteristic feature of the present disclosure is that humidified pulverization is performed so that the oxygen content of the RTB sintered magnet is in the range of 1000 ppm or more and 3500 ppm or less by mass. This makes it possible to suppress both the deterioration of powder particles due to pulverization (nitridation) and oxidation due to humidification, thereby obtaining high magnetic properties. As described above, normally, the increase in the oxygen content of the RTB sintered magnet due to the process after pulverization (mainly the process of producing a sintered body from the fine powder) is small (for example, 50 ppm or more and 300 ppm or less). Therefore, it is possible to adjust the oxygen content of the RTB sintered magnet by the pulverization process.
[0048] Specifically, the humidified inert gas in step (2) can be obtained by adding moisture to the inert gas in an amount of, for example, 0.5 g to 6.0 g per kg of coarsely pulverized powder. If the amount is less than 0.5 g, the deterioration (nitridation) of the powder particles due to pulverization cannot be suppressed, and the magnetic properties may deteriorate. On the other hand, if the amount exceeds 6.0 g, the humidification is too strong, and the oxidation of the powder particles may progress, resulting in a deterioration of the magnetic properties.
[0049] The dew point in the grinding chamber and the amount of coarsely pulverized powder supplied to the jet mill apparatus depend on the grinding time and the size of the jet mill apparatus, but in a preferred embodiment, the inert gas is humidified so that the dew point during grinding is −55° C. or higher and −30° C. or lower. In a further preferred embodiment, the rate at which the coarsely pulverized powder is supplied to the jet mill apparatus is 35 kg / hour or higher and 180 kg / hour or lower.
[0050] Examples of inert gases are nitrogen, argon, and helium. Among them, nitrogen is the most preferable because it is available at a low cost as a high-purity gas. Therefore, in a preferred embodiment, the inert gas is nitrogen gas. However, as a result of the study by the present inventors, when jet mill pulverization is performed using an inert gas consisting of nitrogen in the conventional method, it was found that when the average particle size of the resulting fine powder becomes 4.5 μm or less, the magnetic properties begin to deteriorate due to nitridation. In particular, it was found that when the average particle size becomes 3.5 μm or less, the deterioration of the magnetic properties due to nitridation may become significant. However, according to the embodiment of the present disclosure, since pulverization is performed in an appropriately adjusted humidified atmosphere, even if nitrogen gas is used as the inert gas, it is possible to suppress both nitridation and oxidation. This is thought to be because, even if the inert gas in the pulverization chamber is mainly nitrogen, by humidifying it so that it contains a specific adjusted amount of moisture, the active surface of the particles that appear by pulverization can be thinly oxidized before it is nitrided. The increase in oxygen content of the RTB sintered magnet due to the process after fine pulverization (mainly the process of producing a sintered body of the fine powder) is preferably 50 ppm to 300 ppm by mass, more preferably 50 ppm to 200 ppm by mass. To achieve this, wet pressing in a magnetic field or pressing in a magnetic field in an inert gas atmosphere is performed as described below, and the resulting molded body is sintered. The average particle size of the fine powder in the process of obtaining the fine powder is 2.0 μm to 4.5 μm. If it is less than 2.0 μm, the crushed particle size of the fine powder is too small and it may not be possible to prevent the deterioration of the crushing efficiency during jet mill crushing, and if it exceeds 4.5 μm, it may not be possible to obtain high magnetic properties. The crushed particle size of the fine powder is more preferably 2.0 μm to 3.5 μm. By reducing the average particle size, it is possible to improve the magnetic properties.
[0051] <(3) Example of a process for producing a sintered body of fine powder> In a preferred embodiment, the step of producing a sintered body of fine powder includes a step of producing a powder compact from the fine powder by pressing in a magnetic field, and a step of sintering the powder compact. In the case of pressing in a magnetic field, it is preferable to form the powder compact by pressing in an inert gas atmosphere or wet pressing from the viewpoint of suppressing oxidation. In particular, in the case of wet pressing, the surface of the particles constituting the powder compact is covered with a dispersant such as an oil agent, and contact with oxygen or water vapor in the air is suppressed. Therefore, it is possible to prevent or suppress oxidation of the particles by the air before, during, or after the pressing step.
[0052] When wet pressing in a magnetic field is performed, a slurry is prepared by mixing fine powder with a dispersion medium, and the slurry is supplied to a cavity in a mold of a wet pressing device and press-molded in a magnetic field.
[0053] ·Dispersion medium The dispersion medium is a liquid in which the alloy powder can be dispersed to obtain a slurry.
[0054] A preferred dispersion medium used in the present disclosure may be mineral oil or synthetic oil. Although the type of mineral oil or synthetic oil is not specified, if the kinetic viscosity at room temperature exceeds 10 cSt, the increased viscosity may strengthen the bonding force between the alloy powders, which may adversely affect the orientation of the alloy powder during wet compaction in a magnetic field. For this reason, the kinetic viscosity of the mineral oil or synthetic oil at room temperature is preferably 10 cSt or less. If the fractional point of the mineral oil or synthetic oil exceeds 400°C, it may be difficult to remove the oil after obtaining a compact, and the amount of residual carbon in the sintered body may increase, resulting in a deterioration of the magnetic properties. Therefore, the fractional point of the mineral oil or synthetic oil is preferably 400°C or less. Vegetable oil may also be used as the dispersion medium. Vegetable oil refers to oil extracted from plants, and the type of plant is not limited to a specific plant.
[0055] - Preparation of slurry The obtained alloy powder is mixed with a dispersion medium to obtain a slurry.
[0056] The mixing ratio of the alloy powder and the dispersion medium is not particularly limited, but the concentration of the alloy powder in the slurry is preferably 70% or more (i.e., 70% by mass or more) in terms of mass ratio. 3 This is because, at a flow rate of 1000 / sec, the alloy powder can be efficiently supplied into the cavity and excellent magnetic properties can be obtained. The concentration of the alloy powder in the slurry is preferably 90% or less by mass ratio. The method of mixing the alloy powder and the dispersion medium is not particularly limited. The alloy powder and the dispersion medium may be prepared separately, and then the alloy powder and the dispersion medium may be weighed and mixed in a predetermined amount. In addition, when obtaining alloy powder by dry-pulverizing the coarsely pulverized powder with a jet mill or the like, a container containing the dispersion medium may be placed at the alloy powder outlet of the pulverizing device such as a jet mill, and the alloy powder obtained by pulverization may be directly collected in the dispersion medium in the container to obtain a slurry. In this case, it is preferable that the atmosphere inside the container is also made of nitrogen gas and / or argon gas, and the obtained alloy powder is directly collected in the dispersion medium without being exposed to the air to obtain a slurry. Furthermore, it is also possible to wet-pulverize the coarsely pulverized powder in the dispersion medium using a vibration mill, ball mill, attritor, or the like to obtain a slurry consisting of the alloy powder and the dispersion medium.
[0057] The slurry thus obtained is molded in a known wet press to obtain a molded body having a desired size and shape, which is then sintered to obtain a sintered body.
[0058] Sintering process Next, the compact is sintered to obtain a rare earth sintered magnet body (sintered body).
[0059] The compact is preferably sintered at a pressure of 0.13 Pa (10 -3 Torr) or less, preferably 0.07 Pa (5.0 x 10 -4The sintering is carried out at a pressure of 1000 to 1150 Torr or less and at a temperature of 1000 to 1150°C. To prevent oxidation due to sintering, residual gas in the atmosphere may be replaced with an inert gas such as helium or argon. The obtained sintered body is preferably subjected to a heat treatment. The magnetic properties can be improved by the heat treatment. Known conditions can be used for the heat treatment, such as the heat treatment temperature and heat treatment time. The rare earth sintered magnet body thus obtained is subjected to a grinding / polishing process, a surface treatment process, and a magnetization process as necessary to complete the final rare earth sintered magnet.
[0060] In a preferred embodiment, the method for producing an RTB based sintered magnet of the present disclosure further includes a diffusion step of diffusing a heavy rare earth element RH (RH is at least one of Tb, Dy, and Ho) from the surface of the sintered body to the inside. Diffusion of the heavy rare earth element RH from the surface to the inside of the sintered body can efficiently increase the coercive force. As shown in the examples described later, when the diffusion step is performed on a sintered body that has been subjected to the humidification pulverization of the present disclosure, a higher H cJ It was found that the following can be obtained. There is no particular restriction on the method of the diffusion step. Any known method can be adopted. Tb or Dy is preferable as the heavy rare earth element RH. The RTB sintered magnet with these elements diffused therein includes a portion where at least one of the Tb concentration and the Dy concentration gradually decreases from the magnet surface toward the magnet interior. In other words, the fact that the RTB sintered magnet includes a portion where at least one of the Tb concentration and the Dy concentration gradually decreases from the magnet surface toward the magnet interior means that at least one of Tb and Dy is diffused from the magnet surface to the magnet interior. This state can be confirmed, for example, by performing line analysis (line analysis) using energy dispersive X-ray spectroscopy (EDX) from the magnet surface to near the center of an arbitrary cross section of the RTB sintered magnet.
[0061] The concentrations of Tb and Dy are calculated based on the following formula: 14B compound particles) or grain boundaries. In addition, when the measurement site is located at a grain boundary, the concentration of Tb or Dy may vary locally or microscopically depending on the type and distribution of compounds containing Tb or Dy that may be formed at the grain boundary. However, when Tb and Dy are diffused from the magnet surface to the inside of the magnet, it is clear that the average concentration values of these elements at positions with the same depth from the magnet surface gradually decrease from the magnet surface toward the inside of the magnet. In the present disclosure, if at least one of the average concentrations of Tb and Dy measured as a function of depth as a parameter decreases with increasing depth in at least a region from the magnet surface to a depth of 200 μm of the RTB sintered magnet, the RTB sintered magnet is defined as including a portion where at least one of the Tb concentration and the Dy concentration gradually decreases.
[0062] The R content of the RTB sintered magnet finally obtained after a diffusion step in which the heavy rare-earth element RH is diffused from the surface of the sintered body to the inside is preferably 32 mass% or less (27 mass% or more and 32 mass% or less). By making the R content of the RTB sintered magnet 32 mass% or less and the oxygen content 1000 ppm or more and 3500 ppm or less by mass (preferably 1000 ppm or more and 3200 ppm or less, more preferably 1000 ppm or more and 2400 ppm or less, and even more preferably 2000 ppm or more and 2400 ppm or less), better magnetic properties can be obtained.
[0063] The N (nitrogen) content in the RTB sintered magnet finally obtained after the diffusion step is preferably 50 ppm to 600 ppm by mass, more preferably 50 ppm to 400 ppm by mass, and most preferably 100 ppm to 300 ppm by mass. The C (carbon) content in the RTB sintered magnet is preferably 80 ppm to 1500 ppm by mass, and more preferably 80 ppm to 1000 ppm by mass. When the acid oxygen content in the RTB sintered magnet finally obtained after the diffusion step is [O], the carbon content is [C], and the nitrogen content is [N], it is preferable that the following formulas 1 to 3 are satisfied. Equation 1: [O]>[C]>[N], Equation 2: [O]≧1.5×[N], Equation 3: [C]≧1.5×[N]
[0064] Furthermore, the inventors have closely examined the structure of the RTB sintered magnet obtained by the above-mentioned wet milling of the present disclosure, and as a result have found that the grain boundary phase in the RTB sintered magnet comprises a rare earth oxide phase, and that the rare earth oxide phase comprises a rare earth oxynitride phase. They have also found that high magnetic properties can be obtained when the rare earth oxynitride phase has a specific crystal structure and the contents (atomic %) of oxygen {O} and nitrogen {N} satisfy a specific relationship. Furthermore, the effect is particularly notable when a diffusion step is performed in which the heavy rare earth element RH is diffused from the surface to the inside of the sintered body (H due to diffusion). cJ It was found that the effect of improving the magnetization was high. Such a structure can be obtained suitably by the humidified pulverization of the present disclosure, but is not necessarily limited to this. For example, by adjusting the amount of oxygen or nitrogen introduced during jet mill pulverization, it is possible to obtain an RTB-based sintered magnet as described below.
[0065] The RTB based sintered magnet of the present disclosure is 14 An RTB sintered magnet comprising a main phase made of a B compound and a grain boundary phase located at the grain boundaries of the main phase (R is a rare earth element and necessarily includes at least one selected from the group consisting of Nd, Pr and Ce, and T is at least one transition metal and necessarily includes Fe), wherein the main phase of the RTB sintered magnet is R2T 14The average crystal grain size of the B phase is 3 μm or more and 7 μm or less, the RTB sintered magnet contains oxygen, carbon, and nitrogen, the oxygen content by mass is 1000 ppm or more and 3500 ppm or less, and the nitrogen content by mass is 50 ppm or more and 600 pm or less, the grain boundary phase has a rare earth oxide phase, the rare earth oxide phase includes a rare earth oxynitride phase having a NaCl-type crystal structure, and the relationship of {O}>1.8×{N} is satisfied, where {O} is the O content (atomic %) in the rare earth oxynitride phase, and {N} is the N content (atomic %) in the rare earth oxynitride phase. Preferably, the RTB sintered magnet further satisfies the relationship of {C}>{N}×0.5, where {C} is the C content (atomic %) in the rare earth oxynitride phase.
[0066] The ratio of the area of the rare earth oxynitride phase to the area of the rare earth oxide phase is preferably 50% or more.
[0067] R2T, the main phase of RTB-based sintered magnets 14The average crystal grain size of the B phase is 3 μm or more and 7 μm or less (preferably 3 μm or more and 5 μm or less), and the RTB sintered magnet contains oxygen, carbon, and nitrogen, with the oxygen content being 1000 ppm or more and 3500 ppm or less (preferably 1000 ppm or more and 2500 ppm or less) in mass ratio, and the nitrogen content being 50 ppm or more and 600 pm or less in mass ratio. This makes it possible to obtain high magnetic properties. The grain boundary phase in the RTB sintered magnet has a rare earth oxide phase, and the rare earth oxide phase includes a rare earth oxynitride phase having a NaCl type crystal structure. As a result of the study by the present inventors, it was found that the rare earth oxynitride phase having a NaCl type crystal structure is easily bonded with carbon (C). Therefore, it was found that the C amount of the main phase can be reduced by having a rare earth oxynitride phase having a NaCl type crystal structure, and thus high magnetic properties can be obtained. It was also found that the rare earth oxynitride phase having the NaCl type crystal structure does not easily form oxides with heavy rare earth elements (e.g., Tb and Dy). Therefore, when the RTB sintered magnet contains Tb or Dy, the rare earth oxynitride phase having the NaCl type crystal structure in the grain boundary can contain more Tb or Dy in the main phase, and high magnetic properties can be obtained. As shown in the examples described later, the effect is particularly remarkable when a diffusion process is performed in which the heavy rare earth element RH is diffused from the surface to the inside of the sintered body. Furthermore, the rare earth oxynitride phase satisfies the relationship {O}>1.8×{N}, where the content of O (atomic %) in the rare earth oxynitride phase is {O} and the content of N (atomic %) in the rare earth oxynitride phase is {N}. By satisfying such a relationship, nitridation in the RTB sintered magnet is suppressed, and high magnetic properties can be obtained. The NaCl type rare earth oxynitride also forms nitrides with heavy rare earth elements. Therefore, when an RTB sintered magnet contains Tb or Dy, if the O and N contents of the rare earth oxynitride phase having a NaCl-type crystal structure at the grain boundaries satisfy the relationship {O}>1.8×{N}, the formation of nitrides with the heavy rare earth elements is suppressed, and more Tb and Dy can be contained in the main phase, resulting in high magnetic properties. As shown in the examples described later, this effect is particularly noticeable when a diffusion step is performed in which the heavy rare earth element RH is diffused from the surface of the sintered body to the inside.
[0068] In addition, preferably, when the C content (atomic %) in the rare earth oxynitride phase is {C}, by satisfying the relationship {C}>{N}×0.5, the C amount in the main phase can be reduced and higher magnetic properties can be obtained.
[0069] The ratio of the area of the rare earth oxynitride phase to the area of the rare earth oxide phase is preferably 50% or more. By making the area ratio of the rare earth oxynitride phase to the area of the rare earth oxide phase 50% or more, the magnetic properties can be further improved. Preferably, the ratio of the area of the rare earth oxynitride phase to the area of the rare earth oxide phase is 70% or more, and more preferably 90% or more.
[0070] Whether or not "the grain boundary phase in the RTB sintered magnet has a rare earth oxide phase, and the rare earth oxide phase includes a rare earth oxynitride phase having an NaCl-type crystal structure" can be confirmed, for example, by observing diffraction peaks and patterns specific to the NaCl-type crystal structure through diffraction measurement using X-rays, neutrons, electron beams, or the like.
[0071] Whether or not "the rare earth oxynitride phase satisfies the relationship {O}>1.8×{N}, where the O content (atomic %) in the rare earth oxynitride phase is {O} and the N content (atomic %) in the rare earth oxynitride phase is {N}" can be confirmed, for example, by performing point, line, or area analysis of the oxide phase using EDX (energy dispersive X-ray analysis) or WDX (wavelength dispersive X-ray analysis).
[0072] Whether or not "the ratio of the area of the rare earth oxynitride phase to the area of the rare earth oxide phase is 50% or more" can be confirmed, for example, by performing EDX or WDX mapping in a certain field of view, color-coding the rare earth oxide phase using commercially available software, and then color-coding the rare earth oxynitride phase within that, and counting the number of pixels of each phase color. EXAMPLES
[0073] The present disclosure will be described in more detail with reference to examples, but the present disclosure is not limited thereto.
[0074] Example 1 Alloys for RTB sintered magnets were produced by strip casting so as to have the compositions of RTB sintered magnets shown in Samples No. 1 to 13 in Table 1 (excluding O, C, and N). The obtained alloys were coarsely pulverized by hydrogen pulverization to obtain coarsely pulverized powders. The average particle size of the coarsely pulverized powders was measured. The average particle size was in the range of 200 μm to 400 μm. In this disclosure, the average particle size means the particle size (median diameter) at which the cumulative particle size distribution (volume basis) from the small particle size side is 50%. The average particle size (d50) was measured using a particle size distribution measuring device "HELOS&RODOS" manufactured by Sympatec under the following conditions: dispersion pressure: 4 bar, measurement range: R2, calculation mode: HRLD.
[0075] The coarsely pulverized powder was fed into the jet mill device 100 of FIG. 1 and pulverized to obtain a fine powder. The pulverization conditions are shown in Table 2. No. 2 in Table 2 was humidified and pulverized by adding 1.5 g of moisture per 1 kg of the coarsely pulverized powder to an inert gas, and the amount of the coarsely pulverized powder supplied to the jet mill device was 64.0 kg / h. No. 1 and No. 3 to 13 are similarly described (No. 1 was pulverized without humidification). In this embodiment, nitrogen gas was used as the inert gas. The average particle size of the obtained fine powder is shown in Table 2. The fine powder was immersed in a mineral oil having a fractional point of 250° C. and a kinetic viscosity of 2 cSt at room temperature in a nitrogen atmosphere to prepare a slurry. The slurry concentration was 85% by mass. The obtained slurry was molded (wet molding) in a magnetic field to obtain a molded body. In addition, a so-called perpendicular magnetic field molding device (horizontal magnetic field molding device) in which the magnetic field application direction and the pressure direction are perpendicular to each other was used as the molding device. The obtained green body was sintered in a vacuum at 1040°C (a temperature at which sufficient densification by sintering occurs) for 4 hours to obtain a sintered body. The density of the sintered body was 7.5 Mg / m 3The results were as above. The sintered body was then subjected to a heat treatment in which it was held at 800°C for 2 hours, cooled to room temperature, and then held at 500°C for 2 hours and cooled to room temperature to obtain a sintered body (RTB sintered magnet). The components of the obtained sintered magnet were determined. The contents of Nd, Pr, B, Co, Al, Cu, Ga, and Zr were measured by ICP atomic emission spectrometry. Furthermore, the O (oxygen content) was measured by gas fusion-infrared absorption method, the N (nitrogen content) by gas fusion-thermal conduction method, and the C (carbon content) by combustion-infrared absorption method, all using a gas analyzer. The O, C, and N contents are in ppm by mass. The results are shown in Table 1. The sintered magnet was machined to prepare samples measuring 7 mm in length, 7 mm in width, and 7 mm in thickness, and the B content of each sample was measured using a BH tracer. r and H cJ The measurement results are shown in Table 3. As shown in Table 1, all of the examples of the present invention satisfy the formulas 1 to 3 of the present disclosure. Furthermore, the average crystal grain size of each sample was measured using EBSD (the average value of the equivalent circle diameters of crystal grains evaluated for each of approximately 5700 to 5800 particles) and was between 4.1 and 4.3 μm.
[0076] [Table 1]
[0077] [Table 2]
[0078] [Table 3]
[0079] As shown in Tables 1 and 2, Nos. 1 to 5 have almost the same composition except for C, O, and N, and the average particle size of the fine powder obtained by jet mill pulverization is also almost the same. As shown in Table 3, all of the examples of the present invention (Nos. 2 to 4) have better magnetic properties than No. 1, which was not humidified and pulverized. It has been believed in the past that, with almost the same composition and particle size, an increase in the amount of oxygen would result in a decrease in magnetic properties. However, as shown in Nos. 1 and 2 to 4, within the oxygen content range of the RTB sintered magnets disclosed herein, the magnetic properties are in fact improved (H cJ The results of Tables 2 and 3 show that in order to obtain higher grindability, the oxygen content of the RTB sintered magnet is preferably 1700 ppm or more. Furthermore, as shown in Table 3, all of the examples of the present invention have a Br≧1.33T and H cJ High magnetic properties of ≧1200kA / m are achieved.
[0080] Example 2 The sintered bodies No. 1 to 3 in Example 1 were prepared. The sintered bodies were subjected to a diffusion process in which a heavy rare earth element RH was diffused from the surface of the sintered body to the inside. Specifically, the raw materials of each element were weighed so as to have a composition of Pr80Tb10Ga7Cu3 in mass ratio, and the raw materials were melted to obtain a ribbon or flake-shaped alloy by a single roll super-quenching method (melt spinning method). The obtained alloy was pulverized in an argon atmosphere, and then passed through a sieve with an opening of 425 μm to prepare a diffusion alloy powder. The sintered bodies No. 1 to 3 in Table 1 were cut and ground to obtain a cube of 7.2 mm × 7.2 mm × 7.2 mm. Next, the diffusion alloy was scattered on the entire surface of the sintered bodies No. 1 to 3 in an amount of 2.5 mass% relative to 100 mass% of the RTB sintered magnet. Thereafter, heat treatment was performed for 10 hours at 900°C in reduced pressure argon controlled at 50 Pa, and then cooled to room temperature. Further heat treatment was performed for 3 hours at 500°C in reduced pressure argon controlled at 50 Pa to produce post-diffusion RTB sintered magnets (Nos. 20 to 23).
[0081] The magnetic properties of the resulting RTB sintered magnet after the diffusion step were measured in the same manner as in Example 1. The results are shown in Table 4. cJ The improvement value of △H in Table 4 cJ No. 6 in Table 4 shows the H cJ From the value (1826 kA / m), the H cJ The value is obtained by subtracting the value (1139 kA / m) from the Tb concentration. Other values are shown in the same manner. When a line analysis was performed using energy dispersive X-ray spectroscopy (EDX) from the surface to near the center of a cross section of an RTB sintered magnet, it was confirmed that the magnet included a section where the Tb concentration gradually decreased from the surface toward the interior of the magnet.
[0082] [Table 4]
[0083] As shown in Table 4, the present invention examples (No. 21 and No. 22) in which the diffusion process was carried out on the sintered body that was subjected to the humidification and grinding of the present disclosure had a higher ΔH than the comparative example (No. 20) in which the diffusion process was carried out on the sintered body that was not subjected to the humidification and grinding. cJ has been obtained.
[0084] The compactibility of the fine powders prepared under the conditions of No. 1 to 4 and No. 6 and 7 in Table 1 was confirmed. The results are shown in Table 5. The compaction pressure shown in Table 5 is the pressure at which the density of the compact is 4.1 g / cm 3 (ρg=4.1g / cm 3 Therefore, the lower the molding pressure, the better the compressibility and moldability.
[0085] [Table 5]
[0086] As shown in Table 5, all of the examples of the present invention had lower molding pressures and better compressibility than the comparative examples, with a molding pressure of 0.20 kgf / cm 2 In particular, Nos. 4 to 7 had a molding pressure of less than half that of the comparative example, resulting in a significant improvement in compressibility of 0.15 kgf / cm. 2 Therefore, the oxygen content of the RTB sintered magnet is preferably 2000 ppm or more by mass. r and H cJ ), the oxygen content of the RTB sintered magnet is preferably 2000 ppm or more and 2400 ppm or less in mass ratio.
[0087] Example 3 In the same manner as in Example 1, alloys for RTB sintered magnets were prepared so as to have the compositions of RTB sintered magnets shown in Samples No. 23 to 26 in Table 6. The obtained alloys for RTB sintered magnets were coarsely pulverized in the same manner as in Example 1 to obtain coarsely pulverized powder. The obtained coarsely pulverized powder was pulverized in the same manner as in Example 1 to obtain fine powder. The pulverization conditions are shown in Table 7. The obtained fine pulverized material was molded, sintered, and heat-treated in the same manner as in Example 1 to obtain an RTB sintered magnet. The components of the obtained sintered magnet were determined in the same manner as in Example 1. The contents of O, C, and N are in ppm by mass. The results are shown in Table 6. As shown in Table 6, Samples No. 23 and 24 have almost the same composition except for O, C, and N. Similarly, Samples No. 25 and 26 have almost the same composition except for O, C, and N.
[0088] The magnetic properties of the obtained RTB sintered magnets are shown in Table 8. r H cJ " is the B at room temperature (23℃) r and H cJ The value is "140℃ H cJ " is H at 140℃ cJ These are the values of B r , H cJ The value of was measured by machining the heat-treated RTB sintered magnets to obtain samples of 7 mm x 7 mm x 7 mm using a BH tracer. Furthermore, the temperature coefficient (β: 23 to 140°C) was calculated as follows. H at 140°C cj H cj140 and H at 23°C cj H cj23 Then, the temperature coefficient = (H cj140 -H cj23 ) / H cj23 / (140℃-23℃)×100% The smaller the absolute value of the temperature coefficient, the more improved the temperature coefficient is.
[0089] As shown in Table 8, the present invention has a B of 1.391T or more. r and H of 1190 KA / m or more cjA β of -0.578 or less was obtained, and when comparing Nos. 23 and 24 and Nos. 25 and 26, which have almost the same composition, the examples of the present invention all have improved temperature coefficients.
[0090] [Table 6]
[0091] [Table 7]
[0092] [Table 8]
[0093] Example 4 In the same manner as in Example 1, alloys for RTB based sintered magnets were produced so as to have the compositions of the RTB based sintered magnets shown in Samples No. 27 and 28 in Table 9. The obtained alloys for RTB based sintered magnets were coarsely pulverized in the same manner as in Example 1 to obtain coarsely pulverized powder. The obtained coarsely pulverized powder was pulverized in the same manner as in Example 1 to obtain fine powder. The pulverization conditions are shown in Table 10. The obtained finely pulverized material was molded, sintered, and heat treated in the same manner as in Example 1 to obtain an RTB based sintered magnet. The components of the obtained sintered magnets were determined in the same manner as in Example 1. The results are shown in Table 9.
[0094] As shown in Table 9, samples No. 27 and 28 have almost the same composition except for O, C, and N. The contents of O, C, and N are in ppm by mass. Table 11 shows the results of measuring the magnetic properties of the obtained RTB sintered magnets. As shown in Table 11, when comparing No. 27 and No. 28, which have almost the same composition, the inventive example (No. 28) has better magnetic properties.
[0095] [Table 9]
[0096] [Table 10]
[0097] [Table 11]
[0098] The grain boundary phase of the RTB sintered magnets No. 27 and No. 28 was observed.
[0099] Specifically, first, the crystal structure of the oxide phase was identified by electron beam diffraction. As a result, it was found that both No. 27 and No. 28 had a NaCl-type oxide phase crystal structure. Next, point analysis and mapping were performed by EDX and WDX. Fe and Nd were analyzed by EDX, and Pr, C, N and O were analyzed by WDX. Point analysis was performed at three points for each oxide phase, and the average values are shown in Table 12. In (A) of Table 12, when the content of O (atomic %) in the rare earth oxynitride phase is {O} and the content of N (atomic %) in the rare earth oxynitride phase is {N}, if the relationship {O}>1.8×{N} is satisfied, it is indicated by a "○" (circle), and if not, it is indicated by an "×". Similarly, in (B), if the relationship {C}>{N}×0.5 is satisfied, it is indicated by an "○" and if not, it is indicated by an "×".
[0100] In addition, the ratio of the rare earth oxynitride phase of the present disclosure was calculated based on the mapping results. First, the mapping intensity of each element was converted to a concentration using software "NMap" manufactured by JEOL Ltd. to match the point analysis results. Next, a scatter diagram analysis was performed using software "Phase Map Maker" manufactured by JEOL Ltd. Specifically, the region where {O}≧10 atomic % was color-coded as the region of the oxide phase, and then the region satisfying formulas (A) and (B) was color-coded to separate the rare earth oxynitride phase of the present disclosure from other oxide phases. Then, the number of pixels of each color in the obtained image was counted to calculate the cross-sectional area of the rare earth oxynitride phase of the present disclosure in the rare earth oxide phase.
[0101] As shown in Table 12, in the example of the present invention (No. 28), the ratio of the area of the rare earth oxynitride phase of the present disclosure to the area of the rare earth oxide phase was 70%, and the example satisfied (A) and (B). In contrast, in the comparative example, the ratio of the area of the rare earth oxynitride phase of the present disclosure was 14%, and the comparative example did not satisfy (A) and (B).
[0102] [Table 12]
[0103] Example 5 Furthermore, the sintered bodies of samples No. 27 and No. 28 were subjected to a diffusion process in which the heavy rare earth element RH was diffused from the surface to the inside of the sintered bodies. Specifically, the raw materials of each element were weighed so that the composition was Nd31Pr50Tb9Ga5Cu5 by mass ratio, and the raw materials were melted and the diffusion alloy powder was prepared by the atomization method. The sintered bodies of No. 27 and No. 28 in Table 1 were cut and ground to form rectangular parallelepipeds of 7.2 mm x 7.2 mm x 4.7 mm (the 4.7 mm direction was the direction of magnetic field application during molding). Next, 2 mass% of the diffusion alloy was sprayed on one side (7.2 mm x 7.2 mm surface) of the sintered bodies of No. 27 and No. 28 relative to 100 mass% of the RTB sintered magnet. Thereafter, heat treatment was performed for 10 hours at 920°C in reduced pressure argon controlled at 50 Pa, followed by cooling to room temperature, and then heat treatment for 3 hours at 450°C in reduced pressure argon controlled at 50 Pa to produce diffused RTB sintered magnets (Nos. 29 and 30). Note that, as in Example 2, it was confirmed that the diffused RTB sintered magnets included a portion where the Tb concentration gradually decreased from the magnet surface toward the magnet's interior.
[0104] The magnetic properties of the resulting RTB sintered magnets (Nos. 29 and 30) after the diffusion step were measured in the same manner as in Example 1. The results are shown in Table 13. cJ The improvement value of △H in Table 13 cJ As shown in.
[0105] [Table 13]
[0106] As shown in Table 13, the example of the present invention (No. 30) which underwent the diffusion process had a higher ΔH than the comparative example (No. 29). cJ Moreover, in the same manner as in Example 4, the grain boundary phase of the RTB sintered magnet after diffusion was observed to determine whether it contained the rare earth oxynitride phase of the present disclosure, and it was confirmed that the composition and the area ratio of the NaCl-type rare earth oxynitride phase were approximately the same as those in Table 12 (RTB sintered magnet before diffusion). [Industrial Applicability]
[0107] The method for producing an RTB based sintered magnet according to the present disclosure can be used to produce permanent magnets for a wide variety of applications, such as voice coil motors (VCMs) for hard disk drives, motors for electric vehicles (EVs, HVs, PHVs), motors for industrial equipment, and other motors, as well as home appliances. [Explanation of symbols]
[0108] 100···Jet mill equipment, 200···Cyclone collection equipment, 300···Bag filter equipment
Claims
1. A method for producing an R-T-B based sintered magnet (R is a rare earth element and necessarily contains at least one selected from the group consisting of Nd, Pr and Ce, and T is at least one transition metal and necessarily contains Fe), comprising the steps of: preparing a coarsely pulverized powder of an alloy for an R-T-B based sintered magnet having an average particle size of 10 μm or more and 500 μm or less; supplying the coarsely pulverized powder to a jet mill device having a pulverization chamber filled with an inert gas to pulverize the coarsely pulverized powder, thereby obtaining a fine powder having an average particle size of 2.0 μm or more and 4.5 μm or less; and preparing a sintered body of the fine powder. The inert gas is humidified in accordance with the amount of the coarsely pulverized powder to be pulverized, and is obtained by providing the inert gas with moisture of 0.5 g to 6.0 g per kg of the coarsely pulverized powder, The method for producing a sintered RTB based magnet, wherein the sintered RTB based magnet has an oxygen content of 1000 ppm or more and 3500 ppm or less by mass ratio.
2. The method for producing a sintered R-T-B based magnet according to claim 1, wherein the R content of the sintered R-T-B based magnet is 31 mass % or less.
3. 3. The method for producing a sintered RTB based magnet according to claim 1, wherein the inert gas is nitrogen gas.
4. 4. The method for producing a sintered R-T-B based magnet according to claim 1, further comprising a diffusion step of diffusing a heavy rare earth element RH (RH being at least one of Tb, Dy, and Ho) from the surface of the sintered body to the inside.
5. The step of preparing a sintered body of the fine powder includes: preparing a powder compact from the fine powder by wet pressing in a magnetic field or by pressing in a magnetic field in an inert gas atmosphere; sintering the powder compact; 5. The method for producing a sintered R-T-B based magnet according to claim 1, comprising:
6. 6. The method for producing a sintered RTB system magnet according to claim 1, wherein the average particle size of the fine powder in the step of obtaining the fine powder is 2.0 μm or more and 3.5 μm or less.
Citation Information
Patent Citations
Manufacture of permanent magnet
JP1992287304A
Manufacture of raw material powder for rare-earth magnet
JP1994140220A
Production of rare earth magnet
JP1996148317A
Manufacture of rear-earth permanent magnet
JP1998022154A
Magnet molding and method of manufacturing the same
JP2011060975A